2010
DOI: 10.1007/s12311-010-0242-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Cerebellar-Interpositus/Red-Nucleus-Motoneuron Pathway During Motor Learning

Abstract: Understanding the role played by the cerebellum in the genesis and control of learned motor responses requires a precise knowledge of interdependent relationships between kinetic neural commands and the performance (kinematics) of the acquired movements. The eyelid motor system is a useful model for studying how simple motor responses are generated and performed. Here, we recorded the activity of interpositus, red nucleus, and/or facial motor neurons during classical eyeblink conditioning, using a delay paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
(98 reference statements)
1
20
1
Order By: Relevance
“…It has also been shown that the activation of IP neurons with GABA antagonists also facilitates unconditioned responses (Chen and Evinger, 2006). A possible explanation for this discrepancy is that most lesion studies performed in rabbits refer to a rostral location of IP neurons related to eyelid responses, a fact not confirmed in many other species (mice, rats, cats, monkeys; Sánchez-Campusano et al, 2011). In all of these species eyelid-related neurons are located in more caudal aspects of the IP nucleus as performed here.…”
Section: Effects Of Acute Inactivation Of the Cerebellar Ip Nucleus Ocontrasting
confidence: 48%
“…It has also been shown that the activation of IP neurons with GABA antagonists also facilitates unconditioned responses (Chen and Evinger, 2006). A possible explanation for this discrepancy is that most lesion studies performed in rabbits refer to a rostral location of IP neurons related to eyelid responses, a fact not confirmed in many other species (mice, rats, cats, monkeys; Sánchez-Campusano et al, 2011). In all of these species eyelid-related neurons are located in more caudal aspects of the IP nucleus as performed here.…”
Section: Effects Of Acute Inactivation Of the Cerebellar Ip Nucleus Ocontrasting
confidence: 48%
“…6C) (Gauck and Jaeger 2000;Boele et al 2010;Witter et al 2013). The simple spike suppression starts well before the onset of the conditioned eyeblink response (Ten Brinke et al 2014), but the extent to which the subsequent increase in cerebellar nuclei firing determines the onset of the eyelid closure or dynamically controls the closure in an online fashion is not known (Sánchez-Campusano et al 2011). Presumably, the rebound in the activity of cerebellar nuclei neurons following simple spike suppression is facilitated by excitatory inputs from mossy fiber and/or climbing fiber collaterals (Fig.…”
Section: Motor Learning In a Zebrin-negative Module: Eyeblink Conditimentioning
confidence: 99%
“…The programs/scripts used here were developed by one of us (R.S.-C.) with the help of MATLAB (The MathWorks, Natick, MA, USA) routines [3].…”
Section: Methodsmentioning
confidence: 99%